PERSEPSI WISATAWAN PADA KEBERSIHAN PANTAI SEMINYAK, BALI - Jessica; Andri Wibowo; Jessica Jessica (Journal of Innovation Research and Knowledge, 2026)
Seminyak Beach in Bali is a prime tourist destination attracting both domestic and international tourists. However, the increase in tourist visits and commercial activities along the coastline has also created challenges to the cleanliness of the beach environment. This study aims to analyse tourists' perceptions of Seminyak Beach's cleanliness and identify factors influencing these perceptions. The research method used was a descriptive qualitative approach, based on field observations and semi-structured interviews with 30 tourists (18 foreign, 12 domestic) who visited the beach during the low season (February 2025). Observational data showed that, on average, 63% of respondents rated beach cleanliness as 'fair', 23% as 'good', and 14% as 'poor'. The main factors influencing perceptions were the visual appearance of trash (contributing ± 38%), odour (± 25%), and limited trash facilities (± 20%). Interview results showed that tourists appreciated the cleaning efforts by officers and community volunteers, but considered the cleaning frequency inconsistent. This study recommends strengthening sustainable beach-cleaning management systems, improving cleaning facilities, and conducting awareness campaigns for tourists